Treatment of Tannery Wastewater by Chemical Coagulation and Electrocoagulation - Ulu, Feride; Kobya, Mehmet (Mehmet Sinan Bilgili, 2020)
The purpose of this study was to research the chemical coagulation on wastewater of primary sedimentation basin which belongs to Tanning Industry Wastewater Treatment Plant by using various type chemical substances. Besides, electrocoagulation process was applied on wastewater of primary sedimentation basin and final sedimentation basin. For this purpose, during chemical coagulation experiments, Al-base coagulants (alum and AlCl3) and Fe-base coagulants (Fe2(SO4)3 and FeCl3) were used as coagulated materials. The coagulate dosage and pH range effects to the efficiency of treatment was researched. During these experiment more efficiency has observed when the coagulate materials including ferric salt were used. The best result was obtained when pH 7.5. An electrocoagulation (EC) reactor using iron plate electrodes were designed. The effect of parameters such as pH, current density and operating time on COD, total S, total Cr, NH3-N and SS removal were investigated. At the end of EC process 30% COD and 60% SS disposal were obtained in the primary sedimentation basin of wastewater. In the same condition, 35% COD and 85% SS disposal were obtained in the final sedimentation basin of wastewater. Disposal of NH3-N was calculated 20% for both wastewaters. However, due to the results were not quite satisfactory, for application of disposal of NH3-N another system improvement has started.
5th Eurasian Waste Management Symposium (EWMS) -- OCT 26-28, 2020 -- Istanbul, TURKEY
Keywords: Chemical coagulation; Electrocoagulation; Tannery wastewater